PENYALINAN DAN PENYADURAN NASKAH PAKUALAMAN PADA MASA PAKU ALAM V (1878—1900) - Saktimulya, S.R. (Balai Bahasa Jawa Timur, 2014)
The purpose of this study is to discover the purpose of Paku Alam V, the supreme ruler of Kadipaten Pakualaman Yogyakarta (1878-1900) in initiating the recopying of classic manuscripts by changing a number their r?r?nggan (illustrations), while at the same time adapting texts from newspapers to be written in Javanese with Javanese characters. In this study, the researcher used philology and hermeneutics approach. Philology was used because the research objects were old manuscripts. Paul Ricoeur's hermeneutics was utilized as a means to understand the text. The results of the study show that the creation of a number of copies at that time reflects the policies of Paku Alam V. Some of the policies were in the fields of economics and education. The economic slump at the end of the reign of Paku Alam IV forced Paku Alam V to live frugally. Despite this situation, Paku Alam V worked hard to support his daughters to study overseas and sought for the welfare of his people by providing good examples to encourage them to work hard. They were driven to have a modern way of thinking, but they should still uphold Javanese teachings handed down from Pakualaman's ancestors. The purpose of this study is to discover the purpose of Paku Alam V, the supreme ruler of Kadipaten Pakualaman Yogyakarta (1878-1900) in initiating the recopying of classic manuscripts by changing a number their r?r?nggan (illustrations), while at the same time adapting texts from newspapers to be written in Javanese with Javanese characters. In this study, the researcher used philology and hermeneutics approach. Philology was used because the research objects were old manuscripts. Paul Ricoeur's hermeneutics was utilized as a means to understand the text. The results of the study show that the creation of a number of copies at that time reflects the policies of Paku Alam V. Some of the policies were in the fields of economics and education. The economic slump at the end of the reign of Paku Alam IV forced Paku Alam V to live frugally. Despite this situation, Paku Alam V worked hard to support his daughters to study overseas and sought for the welfare of his people by providing good examples to encourage them to work hard. They were driven to have a modern way of thinking but they should still uphold Javanese teachings handed down from Pakualaman's ancestors. Key Words: copying; adaptation; r?r?nggan (illustration); Javanese teachings; a modern way of thinking Abstrak: Tujuan penelitian ini adalah mengetahui maksud Paku Alam V, penguasa tertinggi Kadipaten Pakualaman Yogyakarta (1878?1900) memprakarsai penyalinan kembali naskah?naskah adiluhung dengan mengubah sejumlah r?r?nggan ?ilustrasi??nya, sekaligus menyadur teks dari surat kabar untuk ditulis dalam bahasa dan aksara Jawa. Dalam penelitian ini digunakan pendekatan filologi dan hermeneutika. Filologi digunakan karena objek penelitian adalah naskah karya masa lampau; sedangkan hermeneutika pemikiran Paul Ricoeur dimanfaatkan sebagai sarana untuk memahami teksnya. Hasil penelitian menunjukkan bahwa penciptaan sejumlah naskah pada waktu itu mencerminkan kebijakan Paku Alam V, antara lain dalam bidang ekonomi dan pendidikan. Keterpurukan ekonomi pada masa akhir Paku Alam IV menyebabkan Paku Alam V harus hidup hemat. Meski demikian, Paku Alam V berusaha keras memajukan pendidikan anak-anak perempuannya ke luar negeri dan menyejahterakan warganya dengan memberikan keteladanan agar mau bekerja keras. Mereka didorong berpikiran modern namun tetap harus memegang teguh piwulang Jawa yang diberikan oleh para leluhur Pakualaman